Direktori Penerbitan, Percetakan, dan Toko Buku di Kota Padang - Mardianti, Mardianti; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discusses how Making Directories Publishing, Printing and Book Stores in the city of Padang. The purpose of this paper is to find a way of making a directory of publishing, printing, and book stores in the city of Padang. The method used in this paper is the observation of spaciousness to know the publishing, printing, and any bookstore in the city of Padang. Based on analyzing the data, it was concluded the following matters. First, based on the findings in the field is known that there are nine pieces of publishing, printing 44, and 12 bookstores in the city of Padang. Second, as for the steps in the manufacturing directory publishing, printing, and book stores in the city of Padang are: (a) data collection; (b) notes the existing data into Microsoft Word; (c) determine the subject; (d) the classification or grouping; (e) Preparation of a directory.Keyword: directory, publishing, printing, book store.